2020
DOI: 10.1136/bmjopen-2020-042946
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of X-ray versus CT in COVID-19: a propensity-matched database study

Abstract: ObjectivesTo identify the diagnostic accuracy of common imaging modalities, chest X-ray (CXR) and CT, for diagnosis of COVID-19 in the general emergency population in the UK and to find the association between imaging features and outcomes in these patients.DesignRetrospective analysis of electronic patient records.SettingTertiary academic health science centre and designated centre for high consequence infectious diseases in London, UK.Participants1198 patients who attended the emergency department with paire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 33 publications
(30 reference statements)
1
91
1
2
Order By: Relevance
“…It is of note that all Chinese and French patients were evaluated by CT scan as radiological tests. Borakati et al [ 78 ] studied the diagnostic accuracy of X-ray versus CT in COVID-19. Following these authors, the sensitivity and specificity of CXR for COVID-19 diagnosis were 0.56 and 0.60 and for CT scans, 0.85 and 0.50, respectively, concluding that CT has substantially improved diagnostic performance over CXR and CT should be strongly considered in the initial assessment for suspected COVID-19 [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of note that all Chinese and French patients were evaluated by CT scan as radiological tests. Borakati et al [ 78 ] studied the diagnostic accuracy of X-ray versus CT in COVID-19. Following these authors, the sensitivity and specificity of CXR for COVID-19 diagnosis were 0.56 and 0.60 and for CT scans, 0.85 and 0.50, respectively, concluding that CT has substantially improved diagnostic performance over CXR and CT should be strongly considered in the initial assessment for suspected COVID-19 [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Borakati et al [ 78 ] studied the diagnostic accuracy of X-ray versus CT in COVID-19. Following these authors, the sensitivity and specificity of CXR for COVID-19 diagnosis were 0.56 and 0.60 and for CT scans, 0.85 and 0.50, respectively, concluding that CT has substantially improved diagnostic performance over CXR and CT should be strongly considered in the initial assessment for suspected COVID-19 [ 78 ]. This could be due either for the higher availability to perform chest CT in the various countries previously commented, along with the novelty suffered by China, as they were the first to face a new and unknown disease, therefore precise radiological tests with higher diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR is currently the gold standard diagnostic practice to detect viral infection [ 8 ]. However, the standard confirmatory clinical RT-PCR test to detect COVID-19 is manual, complex, laborious, costly, and ineffective [ 9 , 10 ]. Moreover, the limited availability of test kits and domain experts further hamper the situation.…”
Section: Introductionmentioning
confidence: 99%
“…In the current framework, chest X-ray (CXR) and chest Computed Tomography (CCT) can also effectively be used to diagnose COVID-19 [ 11 , 12 ]. However, CCT due to 3D image and contrast dyes shows a significantly improved performance in COVID-19 diagnosis in comparison to simple 2D CXR [ 9 ]. In the meanwhile, CT scans of COVID-19 infected patients show diverse features and manual interpretation of these scans with subtle variations is quite challenging [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis by Kim et al [ 101 ] reported a pooled sensitivity for chest CT of 94%, with a pooled specificity of 37%. Compared with CXR, chest CT showed increased sensitivity for COVID-19 pneumonia, with improved diagnostic performance [ 102 ]. Borakati et al [ 102 ] reported no difference in specificity between the two modalities.…”
Section: Chest Ctmentioning
confidence: 99%